Detection of Toxoplasma Gondii DNA by PCR following microwave treatment of Serum and whole blood - Meganathan, P.; Singh, S.; Lau, Y.L.; Singh, J.; Subrayan, V.; Nissapatorn, V. (2010)
Detection of Toxoplasma gondii in blood by means of the polymerase chain reaction (PCR) may facilitate early diagnosis of toxoplasmosis in different groups of patients. We evaluated this approach in 42 patients presenting with ocular or psychotic diseases by comparing the sensitivity and specificity of PCR after heat treatment using a microwave oven with a standard genomic DNA extraction method for paired serum and whole blood samples. The presence of serum IgM and IgG antibodies against T. gondii was detected using a standard commercial enzyme-linked immunosorbent assay and enzyme immunoassay for IgG avidity test. Of 42 whole blood samples, PCR after microwave treatment was positive in 8 samples with a sensitivity of 73 and specificity of 100 compared to 11 samples positive by the extraction method. Although none of 42 sera samples was PCR positive by the extraction method, 7 specimens were positive after microwave treatment. This is the first study to use a microwave heat treatment, which is simple, rapid and a promising alternative method, in detecting small amounts of T. gondii DNA in human blood. Furthermore, irradiation of blood samples with microwaves allows incorporation of PCR into a practical tool for routine clinical assessment of patients with Toxoplasma infection.